La moda "I" - Cubillos Vergara , María Carolina (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
The increasing influence of femenine fashion in Medellin between 1930 and 1960 was an interest topic in the conservative press. In this way, newspapers and magazines like como El Heraldo Católico, El Pueblo, El Obrero Católico, La Familia Cristina and Antioquia por María, the catholic church and some conservative section of the city. Show their thinking about fashion . These ideas show ir like a real threat for familiar stability to have a negative influence on woman, main banner of religión that had the important dury to transmit values and catholic mandares.